Transcendência e religião no pensamento de H. C. de Lima Vaz - Oliveira, Juliano de Almeida (2014)
This work analyzes the theme of transcendence and religion in Lima Vaz s thought. Considering a crisis involving modernity and metaphysical and ethical nihilism, the Brazilian philosopher suggests transcendence as an outflow of modern immanentism and a new horizon of meaning for the human existence. As a Christian philosopher, through his theoretical and experiential elaborations, Lima Vaz reflects on religion as a medium in which it s possible to cultivate the seeds of meaning discovered in the research about transcendence in general. This is an investigation in the intersection of Philosophical Anthropology, Metaphysics and Philosophy of Religion. The itinerary of this work begins with the recollection of the context of modernity and its crisis and the historical development of the concept of the transcendence. The human being is systematically seen as capable of going beyond itself, through a spiritual dynamism that aims to a transcendent horizon, which can be seen as formal (Being, True, Good) and actual (the divine Absolute). Doing metaphysics means pursuing that horizon, whose starting point is the intuition of being in the judicative act, the great discovery is the being as actus essendi and the point of arrival is the Esse ipsum subsistens, for which the analogy is a privileged way of approximation. In this route, Thomas Aquinas is a clairvoyant and enlightening company. Finally, the self-transcendence of the human spirit is seen not only in its theoretical dimension of thought, but as a religious experience of the divine Absolute which, in turn, opens new perspectives for reflection, seeking harmony between faith and reason. The work seeks to bring the honest confrontation of the issue of transcendence as performed by Lima Vaz, while allowing an exit from nihilism towards a plausible sense for human existence, understood as rational and free